Evaluation Of E-Learning Video in Sasak Alus Language - Anwar, Zul; Wibawa, Basuki; Ibrahim, Nurdin (International Journal of Engineering and Technology, 2019)
The learning process is a system which consists of various components that work together to achieve the goal. One of the components of the system is learning resources.Learning resources can be distinguished in general into two, namely learning resources by design and by utilization. Learning resources that are formulated and developed can be in the form of videos. The e-learning video of the development results before being used is first evaluated by being validated and then revised until the learning resources are appropriate to be used. Once it is considered that it can be used, the use is disseminated. This research is an evaluation study consisting of four steps. First, one-to-one evaluation by expert; second, one-to-one evaluation by learners; third, small group evaluation; and fourth, field trials.Data were collected using questionnaires then analyzed using descriptive statistics. The results of the evaluation of the source of learning from video in one to one evaluation by experts then obtained an average value of 79.6, the results of one to one evaluation by learners then obtained a value an average of 83.8, the results of a small group trial amounted to 80.0, and the results of field trials were 85.8. Based on the results of these trials, it can be concluded that the learning resources of the videos developed are appropriate for use in the process of learning of local subject.